GAMBARAN PENETAPAN KEBIJAKAN DAN PERENCANAAN KESELAMATAN DAN KESEHATAN KERJA DI RSUD BAHTERAMAS PROVINSI SULAWESI TENGGARA TAHUN 2020 - Pitrah Asfian; Nurhadisa Nurhadisa; Fifi Nirmala G (Jurnal Kesehatan dan Keselamatan Kerja Universitas Halu Oleo, 2021)
The hospital is a workplace where there are many potential hazards. To minimize potential hazards that will impact health workers, visitors and patients, it is necessary to establish HOHS policies and plans. The purpose of this study was to find out how the description of OHS policy making and planning at the Bahteramas Hospital. This type of study was a qualitative descriptive study with a phenomenological approach. Determination of informants used purposive sampling technique. Informants included Chairperson of the HOHS Committee, Head of the OHS Division, Head of the ICU Room Installation and Head of the Inpatient Room. Primary data obtained by triangulation techniques, namely interviews, observation and documentation. Variables consist of policy setting, organization, support for facilities and infrastructure, risk management and control of potential hazards. The results shows that there is no written policy, but an organization was formed which was marked by the issuance of Director Decree number 725 in 2019 concerning the HOHS organizational guidelines and there is a determination of funding support such as fees from BLUDs, activity proposals and RKA, support for facilities and infrastructure such as APAR, hydrants, evacuation routes, fire alarm systems. OHS planning is to carry out risk management by using checklists and priority problems and controlling potential hazards to health workers by setting work shifts and using PPE, while visitors and patients are given safety such as cleaning wet floors. Conclusion, at Bahteramas Hospital, there is no written policy establishment but there is risk management and control of potential hazards